Implementasi Good Coorporate Governance, Good Governance dan Kepemimpinan Situasional Terhadap Kinerja Pegawai - Wattimena, Muhammad Amin (Public Policy, 2020)
This study aimed at finding out and analyzing the effect of good corporate governance, good governance and situational leadership on employees’ performance (a study at public hospital in Masohi region). The hypotheses formulated in this study were: 1) Good corporate governance had positive effects on employees’ performance at public hospital in Masohi; 2) Good governance had positive effects on employees’ performance at public hospital in Masohi; 3) Situational leadership had positive effects on employees’ performance at public hospital in Masohi. The collected data were analyzed by regression analysis. The results showed that 1) Good corporate governance significantly had positive effects on employees’ performance shown by the value 4.19; 2) Good governance significantly had positive effects on employees’ performance by the value 4.17; 3) Situational leadership significantly had positive effects on employees’ performance shown by the value 3.94; 4) Good corporate governance, good governance and situational leadership simultaneously had positive effects on employees’ performance at public hospital in Masohi shown by the value 4.07. The results of testing proved that all four hypotheses in this study were accepted